2016
DOI: 10.2807/1560-7917.es.2016.21.29.30295
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced surveillance of Clostridium difficile infection occurring outside hospital, England, 2011 to 2013

Abstract: There are limited national epidemiological data for community-associated (CA)-Clostridium difficile infections (CDIs). Between March 2011 and March 2013, laboratories in England submitted to the Clostridium difficile Ribotyping Network (CDRN) up to 10 diarrhoeal faecal samples from successive patients with CA-CDI, defined here as C. difficile toxin-positive diarrhoea commencing outside hospital (or less than 48 hours after hospital admission), including those cases associated with community-based residential c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 35 publications
6
32
1
Order By: Relevance
“…Around the same time, a ten fold increase was noted in North America (Jhung et al, 2008). Similar increases and occasional outbreaks were subsequently recorded throughout Europe (Barbut et al, 2007; Bauer et al, 2011; Burns et al, 2010) and C. difficile RT078 has recently increased to 4.4%, 9.7% and 8.1% of total Clostridium difficile infection cases in North America, England and Scotland, respectively (Lessa et al, 2015; Mulvey et al, 2010; Fawley et al, 2016; Health Protection Scotland (2017). Three distinctive features of RT078-associated Clostridium difficile infection raise specific concerns, namely: increased severity of disease with the highest genotype-specific mortality rate (Goorhuis et al, 2008; Walker et al, 2013), a higher proportion of community-associated disease, and more infections in younger age groups compared with other genotypes (Lessa et al, 2015; He et al, 2013; Taori et al, 2014).…”
Section: Introductionmentioning
confidence: 56%
“…Around the same time, a ten fold increase was noted in North America (Jhung et al, 2008). Similar increases and occasional outbreaks were subsequently recorded throughout Europe (Barbut et al, 2007; Bauer et al, 2011; Burns et al, 2010) and C. difficile RT078 has recently increased to 4.4%, 9.7% and 8.1% of total Clostridium difficile infection cases in North America, England and Scotland, respectively (Lessa et al, 2015; Mulvey et al, 2010; Fawley et al, 2016; Health Protection Scotland (2017). Three distinctive features of RT078-associated Clostridium difficile infection raise specific concerns, namely: increased severity of disease with the highest genotype-specific mortality rate (Goorhuis et al, 2008; Walker et al, 2013), a higher proportion of community-associated disease, and more infections in younger age groups compared with other genotypes (Lessa et al, 2015; He et al, 2013; Taori et al, 2014).…”
Section: Introductionmentioning
confidence: 56%
“…This is consistent with a small portion of case patients requiring hospitalization and no occurrence of severe complications (eg, colectomy). Among the predominant strains in this study, ribotypes 020, 056, and 015 were also detected among CA-CDI in England [36], whereas ribotype 106 was more prevalent overall in Scotland [37]. Notably, high frequencies of resistance to clindamycin, fluoroquinolones, and cephalosporins in ribotype 106 and associated outbreaks have been described [37, 38], indicating the need for continued surveillance for changes in the molecular epidemiology of CA-CDI to help guide prevention efforts.…”
Section: Discussionmentioning
confidence: 92%
“…An increase occurred in PCR ribotype diversity over time (Figure 3, panel A and B). Similarly, a study in England indicated that ribotype diversity increased as outbreak-prone types decreased ( 13 ). These results (i.e., the disappearance of major types, increase in type diversity, and decrease in incidence) suggest that hospitals adopted improved infection control during the study period.…”
Section: Resultsmentioning
confidence: 99%